Landscape formation, environmental changes and prehistoric occupation (Jacaré-Guaçu River Lowlands, Araraquara area, Southeast Brazil, Late Pleistocene-Holocene interval): correlation between geomorphological, pedological, geochronological and archaeological data - Cheliz, Pedro Michelutti; Oliveira, Regina Celia (Quaternary and Environmental Geosciences, 2019)
This paper presents a geomorphological, pedological and geochronological characterization and contextualization of geomorphogenetic, chronomorphological and environmental sequences from the Araraquara area (central São Paulo State, Southeast Brazil), and their relationship to lithic material from hunter-gatherer archaeological lithic sites. A special emphasis is given to a detailed study of the lowlands of the Jacaré-Guaçu River (between the cities of Araraquara and Boa Esperança do Sul, São Paulo state, Brazil), near the Boa Esperança II hunter-gatherer archaeological site, BES II, in an area of clear asymmetry of the alluvial plain and adjacent slopes. Data derived from the survey of estimated morphogenetic and environmental dynamics are used to contextualize the archaeological material of the BES II site, which is discussed as being associated with the Pleistocene-Holocene transition (an unusual occupation age for the Brazil southeast). We pointed to alternation between successions linked to a quaternary manifestation of a longer pattern of changes of lateral flatting processes and stability of base level with others linked to vertical incision and adequacy to a new base level. We propose a geomorphological model for the Lowlands of Jacaré-Guaçu River, highlighting the possibility that the asymmetry of the plain would be linked to a wider heterogeneity of its geomorphological context of semidetails, partially correlated with the overlapping of neotectonic influence and environmental fluctuations. It is suggested that data from the physical environment of the above mentioned lowlands are compatible with absolute ages obtained by OSL (lower terrace Ia, 14,500±3000 years BP, basal gravel level of the surface coverings, to 10,900±1500 and 4090±340 years BP at the sandy soils and sediments above the gravel) and 14C (8630 years BP, at the level of gleyed sandy-clay soil of 120 cm deep of the low terraces IIa) on archaeological levels of the low terraces of the Jacaré-Guaçu river, in a context of climatic transition from semi-arid conditions to higher humidity, hydrological changes (ephemeral and torrential channels changing to oscillating regimes of perennial channels, with sets of meanders of variable widths of paleochannels, suggesting climatic changes related to the modifications of the fluvial patterns), successive fluctuations (< 10 m) of base levels and large (500 m) lateral migration of the main river to the north guiding the local chronomorphological successions between Late Pleistocene and Late Holocene. The landscape and fluvial dynamics changes over time has influenced the availability of attributes needed for the hunter-gatherer lifestyle (such as fluctuations in the deposition/exposure of river pebbles used as raw material for tool making). Those oscillations are presented as a contribution to explain alternation between more and less dense archaeological levels along the vertical cuts of the low terraces and the location of exception of the BES II site (installed on a fluvial plain and low terraces in a segment characterized by the rarity of rocky outcrops, while most sites in the Araraquara area are linked to slopes, proximal to rocky outcrops - primary sources of lithics artifacts making) on the geomorphological Araraquara area context